Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae) - Lyon, Robert Gary; Geiger, Matthias F.; Freyhof, Jörg (Zootaxa, 2016)
Garra sindhi, new species, is described from Wadi Andhur in the Dhofar province of the Sultanate of Oman. It is closely related to G. dunsirei and G. smarti, two other species from the same Omani province. It differs from these species by the following combination of characters: breast covered by scales, a shallow hump on back, eyes normally developed and 8–12 gill rakers on the lower limb of the first gill arch.